Technology Framework in Guidance And Counseling Services - Fahriza, Irfan; Supriatna, Mamat; Suryahadikusumah, Ahmad Rofi; Rayaginansih, Syari Fitrah; Nadhirah, Nadia Aulia; Nadya, Aisha (Universitas Mathla'ul Anwar Banten, 2023)
Much research has been done on guidance and counseling technology but only focuses on proving the effectiveness of technology applications in counseling. Unfortunately, research has yet to be found focusing on the proper framework for utilizing technology in guidance and counseling. This paper aims to formulate a framework for using technology in counseling services. A systematic literature review analyzes and combines information from various sources to obtain a comprehensive concept. Reference search results from 2011-2022 using published or perish (PoP) identified 69 references that met the literature criteria. The results of the study show that the use of technology in counseling must be oriented towards improving service quality by paying attention to the aspects: 1) Cultural and communication processes that will occur through technological devices, 2) Provisions and procedures for using technology-based services are to be agreed upon, 3) Readiness of technical knowledge from counselors as a service manager, 4) User experience in the technology application used.